2019
DOI: 10.1109/lra.2019.2891091
|View full text |Cite
|
Sign up to set email alerts
|

High-Speed, Small-Deformation Catching of Soft Objects Based on Active Vision and Proximity Sensing

Abstract: In this letter, we propose a combination of sensing and control modules for catching soft objects (i.e., a marshmallow and paper balloon) at a high speed with small deformation. A paper balloon and marshmallow are deformed by a small force and they have individual differences in terms of softness. Therefore, model-based, small-deformation catching is difficult. To realize small-deformation catching, we used high-speed sensor-based (vision and proximity) control modules without a deformation model of the soft o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…IV-A3). To measure distance and posture more precisely, Koyama et al [70], [71] developed a high-speed, high-precision proximity sensor, as shown in Fig. 11 (b).…”
Section: ) Reflected Light Intensity-type Sensors (O-rli) Usingmentioning
confidence: 99%
See 1 more Smart Citation
“…IV-A3). To measure distance and posture more precisely, Koyama et al [70], [71] developed a high-speed, high-precision proximity sensor, as shown in Fig. 11 (b).…”
Section: ) Reflected Light Intensity-type Sensors (O-rli) Usingmentioning
confidence: 99%
“…A contact situation with a soft object can be detected with very low contact force. The contact detection enabled the catching of very soft objects, namely a marshmallow and a paper balloon, with negligible deformation [71].…”
Section: B Reactive Preshaping and Grasping (At-ii Bt-i)mentioning
confidence: 99%
“…For a conducive object with an area of 100 × 70 millimeters 2 , the sensor could detect it from a distance of 120 millimeters. In addition to the above body-covered proximity skin for human safety, finger-covered proximity skin can be used for secured grasping [98], [99]. As shown in Figure 5(e), Koyama et al [100] developed a high-speed proximity sensor for the robotic fingertips to control the positions and postures of robot hand without contact before grasping, which means there is no fear of damaging the end-effector or the object.…”
Section: ) Capacitive Sensingmentioning
confidence: 99%
“…In a study by Cuevas-Velasquez et al, the researchers used four structured light cameras to track the far-field motion of the object and a robotmounted stereo camera to track the near-field motion [32]. The most sophisticated object tracking setups have used specialised motion capture hardware, designed specifically to track the motion of objects moving in a 3D space [2,25,33,34]. While these systems boast the greatest accuracy and reliability, they are expensive and require a complex environment setup.…”
Section: Prior Workmentioning
confidence: 99%